The complete photo guide to art quilting - Stein, Susan, 1945- (Complete photo guide, 2012)
" This comprehensive how-to book explores all the concepts and techniques involved in creating art quilts, including composition and design; making whole-cloth, pieced, and appliqued art quilts; fabric manipulation and surface design; quilting/stitching; embellishing; and working in a series. Readers will find easy access to information with step-by-step directions and hundreds of full-color photos for clear understanding. Easy projects provide opportunities for the reader to try the techniques, and galleries of art quilts by various fabric artists offer beautiful examples and enticing inspiration. "--